Knowledge, attitude and practice towards hand, foot and mouth disease (HFMD) among nursery governesses in Klang Valley, Selangor - Mahadzar, Siti Aida Shaqirah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Hand, foot and mouth disease (HFMD) is reported as endemic and rank in the third place among other communicable diseases in Malaysia. HFMD outbreak is often found in nurseries and playgroups where children have lots of close contacts with other children. The objective of study is to study the knowledge, attitude and practice of HFMD among nursery governesses of nurseries at public universities and residential areas. Methods: A total of 102 nursery governesses were selected as respondents which include 83 respondents from public university while 26 respondents from residential areas in Klang Valley. Questionnaires were administered to determine socio-demographic, knowledge, attitude and practice on HFMD among the study population. Results: The result indicated that no significance different between knowledge, attitude and practice between two groups (Z = -0.321, p > 0.005; Z = -1.196, p > 0.005; Z = -1.155, p > 0.005) respectively. Furthermore, there was no association between knowledge with practice (p = 0.581, p > 0.005) and attitude with practice (p = 0.298, p > 0.005). Thus, nursery governesses in this study perceived moderate knowledge and attitude level. However for practice, public universities showed better application of practice if compared to residential areas. Conclusion: Hence, it is recommended for the nursery governesses to attend program such as health talk on HFMD occasionally, as it can be efficiently induce positive outcome.